Peran Akuntan Berbasis Values Driven Accounting Sebagai Upaya Penciptaan Daya Saing Berkelanjutan - Siti Amerieska (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
Perception and focus in accounting is need for a paradigm transform in thecome at economic turbulence (the uncertainty of business conditions). Accountant rolenot just as a driver compliance, which has the task of preparing the financial statementonly, but can provide added value driven as business partner.Become business partnerthe accountant should have ability to making decision about performance,profit andstrategic decision.This study aims to provide ideas and strategic thinking to theaccountant to be more involved in the role of value driven. Type in this research is adescriptive study. Discussion of this article about building paradigm as value driven,how to change the focus be performance, change the paradigm of technical cost intostrategic level in the corridors of cost management strategy. In addition to value drivenparadigm that was built in thisarticle also discussed the role of accountant strategicmapping to face the uncertainities of business condition.